Numerical modeling and optimal design of microwave-heating falling film evaporation. (31st August 2021) - Zhang, Yashuang; Zhao, Zhenyu; Li, Hong; Li, Xingang; Gao, Xin
Graphical abstract: Highlights: The microwave-heating falling film evaporation was systematically simulated. The equipment parameters were optimized to achieve uniform and effective heating. The effects of operation conditions on microwave evaporation were analyzed. The flow pattern of spiral falling film overcame the uneven heating problem. Abstract: Microwave-heating falling film evaporation (MFFE) has demonstrated the ability to promote the separation of polar/nonpolar mixtures, but it still faces the challenges of low energy efficiency and uneven heating. The present study optimizes the geometry/operating parameters and flow pattern of MFFE process by coupling the equations of electromagnetic field, fluid flow, heat transfer and liquid evaporation. The accuracy of simulating results is verified experimentally. On the optimization of geometry/operating parameters, the highest energy efficiency is obtained when the liquid film is located at the cylindrical cavity center and only one microwave port is employed. On the design of flow pattern, we employ a rotating spiral falling film flow to MFFE, where the fluid flows along the designed channels. This flow pattern disperses the overheating domains and therefore overcomes the problem of uneven heating. The obtained results can provide guidance for the design and optimization of novel MFFE devices.